Auden's O : the loss of one's sovereignty in the making of nothing - Hass, Andrew (Albany : State University of New York Press, 2013)
"Explores the rise of the idea of nothing in Western modernity and how this idea is transforming and offering new possibilities"--Provided by publisher.
part one. From religion and philosophy to artifice -- part two. Poesis' figure : the making of O -- part III. Looking after O.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Nothing (Philosophy) in literature; Hermeneutics; Postmodernism; Nothing (Philosophy); Electronic books